QoS Routing in Diffserv MPLS Networks - Phang, K.K.; Ling, T.C.; Ang, T.F. (Malaysian Journal of Computer Science, 2009)
With the emergence of new network applications and quality of service (QoS) requirements, current Internet technology that supports best-effort service is clearly insufficient. This paper undertakes a detailed study of dynamic quality of service routing in Differentiated Service (DiffServ) Multiprotocol Label Switching (MPLS) networks. A polynomial time, heuristic dynamic routing algorithm, namely TE-QOSPF-Mix, is proposed to provide a better trade-off between hop-count and bandwidth optimization. The algorithm uses well-defined comparative function in path selection with computational complexity equals the original Dijkstra’s algorithm. A simulator, UMJaNetSim, is built to simulate and evaluate the proposed algorithm. The simulation results indicate that the proposed QoS routing algorithm exhibits better bandwidth acceptance and lower packet loss ratio.